Running out : how global shortages change the economic paradigm - González, Pablo Rafael (Algora, 2006)
A shocking worldwide scarcity of natural resources is about to shake the public from its complacent slumber as the inconvenience of higher gas prices, occasional brown-outs and seasonal water shortages quickly evolve into major, prolonged and widespread shortages of the most elementary commodities. The crisis is being accelerated by mankind's heedless overexploitation and contamination of what's left. Pablo Rafael Gonzalez documents the dire state of the earth's reserves of oil, water and food, as well as the rapid extinction of plant and animal species in 150 tables and graphs drawn largely from World Bank and U.N. reports. Gonzalez, a political analyst, has advised Venezuela's President and Congress for 25 years on energy and resource issues. In this book, he convincingly demonstrates that we are well on the way to exhausting both renewable and nonrenewable natural resources, even if we are in denial about it. This is an unprecedented and mind-boggling challenge for humanity. It also signals a change of the economic paradigm, the lens through which economic experts view the world. Capital, economists like to say, is the scarce factor of production; but starting in this century, it's the scarcity of natural resources that will limit growth. It's time we recognized that fact and dealt with it. Until now, it has been relatively easy to keep on expanding production as mankind conquered the globe, continually gaining access to rich new lands; and rapid population growth has meant there were generally enough hands to do the work. That halcyon era is coming to an end, and economists will have to shift their focus from problems of distribution to problems of resources. The evidence presented in these pages adds up to an urgent plea that governments and other policy-makers abandon some traditional economic ideas and invent radically new approaches in order to shape responsible policies. The tables and graphs make this book invaluable to students and professionals in the fields of history, political science, economics and environmental studies, as well as those involved in or preparing for careers in the geological and extractive industries. Natural resource reserves, production and consumption around the world over the last 100 years, and reductions in forested land, animals and plant species are also tabulated.